EVALUASI KINERJA DOSEN DALAM PERKULIAH SEBAGAI UPAYA MENINGKAT KUALITAS MAHASISWA: Evaluation, Performance, Lecturer, Quality - -, Riswan (LP2M Universitas Nurdin Hamzah, 2018)
This study aimed to evaluate the performance of lecturer Prodi Information Systems in giving lectures, the processed evaluation of faculty performance as an input for the lecturer of the course and the manager of the institution in the decision of the findings in order to improve the quality of lecturers in teaching that will have an impact on the quality of students produced, Research procedures conducted by distributing questionnaires to students as respondents question, more or less there are 173 students involved in filling out the questionnaire. Questionnaire The questionnaire is grouped in three categories of questions: 1). Lecturer As a planner Class; 2) Lecturer As Executive Class; (3) Lecturer As Evaluator Class; with a total of questions as many as 21 items. These results indicate that the performance of lecturers in teaching planner category of four items of questions, three items are on a Likert scale of 4, with intervals of values from 3.40 to 4.19, and the first item is at 3 Likert scale, with the interval 2,60- 3.39. Category Lecturer In Implementing Teaching, faculty positions are on a scale of 4 to 11-item Likert questions asked of 12 items, 1 item is on the Likert scale 3 with an interval from 2.60 to 3.39. Category Lecturer As Evaluator, 3 out of 5 items lecturers are positioned questions on a Likert scale of 4, with intervals of values from 3.40 to 4.19, and the second item on a Likert scale 3 that interval of values from 2.60 to 3.39. Results of the evaluation of faculty performance average for all three categories in the position enough, with the interval of values from 3.40 to 4.19. Policies need to be taken by the management to improve some items that value interval 2.60 to 3.39 in order to improve the quality of students.